Flexible quantum dot light‐emitting devices for targeted photomedical applications. Issue 5 (4th May 2018) - Chen, Hao; Yeh, Tzu‐Hung; He, Juan; Zhang, Caicai; Abbel, Robert; Hamblin, Michael R.; Huang, Yingying; Lanzafame, Raymond J.; Stadler, Istvan; Celli, Jonathan; Liu, Shun‐Wei; Wu, Shin‐Tson; et al.
Abstract: Quantum dot light‐emitting devices (QLEDs), originally developed for displays, were recently demonstrated to be promising light sources for various photomedical applications, including photodynamic therapy cancer cell treatment and photobimodulation cell metabolism enhancement. With exceptional emission wavelength tunability and potential flexibility, QLEDs could enable wearable, targeted photomedicine with maximized absorption of different medical photosensitizers. In this paper, we report, for the first time, the in vitro study to demonstrate that QLEDs‐based photodynamic therapy can effectively kill Methicillin‐resistant Staphylococcus aureus, an antibiotic‐resistant bacterium. We then present successful synthesis of highly efficient quantum dots with narrow spectra and specific peak wavelengths to match the absorption peaks of different photosensitizers for targeted photomedicine. Flexible QLEDs with a peak external quantum efficiency of 8.2% and a luminance of over 20, 000 cd/m 2 at a low driving voltage of 6 V were achieved. The tunable, flexible QLEDs could be employed for oral cancer treatment or diabetic wound repairs in the near future. These results represent one fresh stride toward realizing QLEDs' long‐term goal to enable the wide clinical adoption of photomedicine. Abstract : Flexible quantum dot light‐emitting devices with pure color and high power density have been fabricated on plastic polyethylene naphthalate (PEN) substrates with barrier film encapsulation. Such devices could be used for treatments of oral cancers or diabetic wounds in the near term and hold potential to enable wide clinical adoptions of photomedicines.